Assessment of the effects of the BARF diet on the health of dogs - Maciej Bąkowski; Aleksandra Garbiec; Magda Miklaszewska (Acta Scientiarum: Animal Sciences)
The study aimed to evaluate the BARF (Biologically Appropriate Raw Food) diet based on the mixtures used and to check the impact of the diet on dogs' health by analyzing changes in blood parameters before and after the introduction of a raw diet. The primary research method for this work was an online survey made via the website www.docs.google.com/forms. One hundred questionnaires were obtained in the study. In addition, caregivers of dogs fed the BARF diet were asked to provide laboratory tests, of which 15 results of morphology, biochemistry and expanded ionogram of dogs were obtained before and after introducing the raw diet. The survey results were prepared in Excel and STATISTICA 13.3 (TIBCO Software). In contrast, the blood test results were compared using the Student's T-test for paired samples. Observations and conducted research showed that after introducing the BARF diet to their animals, the respondents noticed many positive effects of their diet. Some of the dogs tested improved their laboratory performance parameters.